Pengaruh Gratitude Journal terhadap Penerimaan Diri Remaja Perempuan dengan Body Image Negatif - Rauf, Sufirah Hidayah; Saman, Abdul; Fitriana, Fitriana; Maslina, Maslina (Paedagogie, 2026)
This study aims to determine the effect of gratitude journals on self-acceptance among female adolescents with negative body image at SMA Negeri 5 Makassar. This study used a quasi-experimental design with a non-equivalent control group, involving 10 subjects in the experimental group who received intervention for 14 days and 10 subjects in the control group who did not receive intervention. Data were collected using Berger's self-acceptance scale and Thomas F. Cash's Multidimensional Body Self Relations Questionnaire-Appearance Scale (MBSRQ-AS) for body image. Data analysis was performed using paired sample t-tests and independent sample t-tests. The results showed a significant difference between the pre-test and post-test scores in the experimental group (p = 0.002 < 0.05) with an average score increase from 67.30 to 78.00. In addition, the results of the independent sample t-test showed a significant difference between the experimental and control groups in the post-test (p = 0.027 < 0.05), where the average score of the experimental group was higher than that of the control group. These findings indicate that gratitude journals have a positive effect on the self-acceptance of adolescent girls with negative body image.